Tracking contemporary microbial evolution in a changing ocean - Brennan, Georgina L.; Logares, Ramiro (Trends in Microbiology, 2023)
Ocean microbes are fundamental for the functioning of the Earth system. Yet, our understanding of how they are reacting to global change in terms of evolution is limited. Microbes typically grow in large populations and reproduce quickly, which may allow them to rapidly adapt to environmental stressors compared to larger organisms. However, genetic evidence of contemporary evolution in wild microbes is scarce. We must begin coordinated efforts to establish new microbial time-series and explore novel tools, experiments, and data to fill this knowledge gap. The development of coordinated microbial ‘genomic’ observatories will provide the unprecedented opportunity to track contemporary microbial evolution in the ocean and explore the role of evolution in enabling wild microbes to respond to global change.
Publisher Copyright: © 2022 Elsevier Ltd
Keywords: DNA; evolution; genomic observatory; global change; metagenomics; microbes; ocean; time-series